BOTULINIUM TOXIN CLINICAL PRACTICE (Fiep Bulletin - online, 2012)
Botulinum toxin, better known by its trade name (Botox ®) is a protein obtained from a bacterium and is used in the medical field to prevent muscle contraction. Initially it was used by the Ophthalmology and Neurology to correct involuntary muscle contractions and a few years ago it began to be used in dermatology for the correction of dynamic wrinkles, with outstanding results. Its cosmetic use has revolutionized today's dermatology aesthetics, besides the treatment forwrinkles and expression marks, it also shows excellent results in the treatment of hyperhidrosis (abnormally increased perspiration) axillary and palmar. The application of botulinum toxin should only be performedby physicians and can be done at the clinic. The substance is injected into specific points of the muscles responsible for facial movements. In order to achieve the desired effects these points are selected according to each person's characteristics as well as the dose must be determined individually. One of the most typical problems related to excessive use of botulinum toxin is the blockade of cholinergic connections in the central nervous system by inhibiting the acetylcholine which results in poor muscle function, when injected directly into muscle it produces weakness or temporary local paralysis.
Keywords: Botulinum Toxin; muscle contraction; treatment